Implementasi Sistem Pengelolaan Program Mentoring Mahasiswa Baru Menggunakan Metode Prototyping - Feby Alya Noor Dhiana; Supriyono Supriyono; Abid Yanuar Badharudin; Achmad Fauzan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The mentoring program at the University of Muhammadiyah Purwokerto (UMP) organized by the Institute for the Study and Practice of Islam (LPPI) was first implemented in the 2004/2005 academic year. This program aims to provide guidance in understanding and internalizing the values of Al Islam and Muhammadiyah (AIK) in daily life. However, until now, it still uses a manual system in recording attendance, managing materials, and monitoring mentoring activities. This causes several problems, such as lack of efficiency in administration, difficulties in data reporting, and limited access for mentors and mentees. Therefore, a website-based information system is needed to optimize mentoring management. This research aims to design a website-based application that simplifies the mentoring administration process, improves the efficiency of attendance recording, and provides easier access for mentors, mentees, coaches, and LPPI admins. The method used in the development of this system is prototyping, which consists of several stages, including gathering needs, making initial prototyping, evaluation by users, and developing the system based on the feedback received. This system is built using website-based technology using the PHP programming language with the Laravel framework, MySQL is used as a database, for the interface display, Tailwind CSS is used. The results of the study show that this mentoring system can improve the efficiency of mentoring administration with an online attendance process, activity reporting in the form of a mentor logbook and activity evaluation. In addition, this system allows LPPI admins to monitor the course of mentoring in real time, so that transparency in mentoring activities increases. The test with black-box testing stated that all the main functions could run well according to their functions, then for the test with SUS (System Usability Scale) it showed that the average value of the SUS test was 84.16 and was stated as very good. It is hoped that the mentoring process at UMP can run more effectively, efficiently, and structured.